Herpes-viral infection: epidemiology, diagnosis, therapy - Yu E Dobrokhotova; E I Borovkova (IP Berlin A.V., 2017)
Genital herpes is a common disease diagnosed in 90% of people and is characterized by a recurring lifelong course. Clinical manifestations are diverse and manifest in 20% of infected people. The gold standard for diagnosis is the detection of virus culture and polymerase chain reaction in real time. Conducting oral antiviral therapy significantly reduces the duration, severity of the disease and the risk of infection of the sexual partner. At the initial episode of genital herpes it is necessary to carry out system antiviral therapy with its earliest start. The effectiveness of the use of acyclovir, valaciclovir and famciclovir is comparable, but only with valaciclovir the efficacy of two-fold daily dosing is proved. For patients with 6 or more episodes of exacerbations per year, suppressive therapy is indicated, the drug of choice is valaciclovir. With a relapse rate of less than 6 per year, it is sufficient to conduct episodic antiviral therapy. Clinical trials have demonstrated comparable efficacy of acyclovir, famciclovir and valaciclovir. The three-day course of valaciclovir (500 mg 2 times a day) is most suitable in view of the high bioavailability and rapid relief of viremia.